Austria : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
A mix of solid economic policies, wage moderation, and an early orientation toward Eastern Europe explain Austria's strong economic performance. The economy has grown strong in 2007 and through the first quarter of 2008. Employment growth remains strong, but the trend of a declining unemployment rate appears to be tapering off. Tighter labor market conditions have not resulted in sharp wage increases; instead negotiated wages for 2008 are up. Austria's external position remains strong, despite a recent decline in competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet